Between the Therapist’s Vulnerability and the Client’s Vulnerability: Building a Therapeutic Intervention Through the Regressive Regions of the Mind - Keini, Noga (Advances in Social Sciences Research Journal, 2021)
The article expands Winnicott ,Balint and other theoretical conceptions in order to describe what happens in a therapist‘s mind so that an intervention can take place. It stresses not only the need to identify the psycho-developmental region where the patient operates, but also how intervention arises in the therapist’s mental regions and engages the relevant mental regions of the patient. It explains the process in which the therapist’s subjective communication with his own mental regions helps the patient establish an initial connection with his regressive areas and even gradually draw closer to them symbolically. The article offers an analysis based on a detailed clinical illustration.